Syntheses, structures and catalytic properties of chiral Co(II) coordination polymers based on (R)-4-(4-(1-carboxyethoxy)phenoxy)benzoic acid. (7th July 2016) - Xu, Xin; Yu, Ying-Hui; Hou, Guang-Feng; Li, Xue-Wei; Ren, Chang-Yue; Ma, Dong-Sheng
Graphical abstract: A series of chiral coordination polymers exhibit second harmonic generation (SHG) efficiency and asymmetrical catalytic properties toward aldol reactions. Abstract: To investigate the construction of novel chiral coordination polymers and the effect of different substituents on the ligands, three complexes, namely [Co(L)(bimb)]·EtOH·H2 O [bimb = 4, 4′-bis((1 H -imidazol-1-yl)methyl)-biphenyl, L = ( R )-4-(4-(1-carboxyethoxy)phenoxy)-3-fluorobenzoic acid (1 ); L = ( R )-4-(4-(1-carboxyethoxy)phenoxy)-3-chlorobenzoic acid (2 ); L = ( R )-4-(4-(1-carboxyethoxy)phenoxy)-3-nitroaniline acid (3 )], have been hydrothermally synthesized and characterized by IR, elemental analyses, thermogravimetric analysis, solid state circular dichroism (CD), powder and single-crystal X-ray diffractions. Structure analysis indicates that complexes1 –3 are isomorphic, featuring two-dimensional (2D) 2-fold interpenetrated sq1 structures. In addition, their second harmonic generation efficiency and catalytic activity for the aldol reaction were investigated.